Factors Influencing Acceptance of Family Planning Acceptors at the Magdalena Pane Clinic - Fransysca, Helena; Tampubolon, Emelia (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Family Planning is an action that helps married couples to prevent unwanted pregnancies, accept the births they want, regulate the interval between pregnancies, and determine the number of children in the family. This study aims to identify the factors for the exclusion of couples of childbearing age as family planning acceptors at the Magdalena Pane Clinic in 2021. This study used a descriptive design using a cross sectional approach. The sample is 71 respondents. The research was conducted from May 2021 to September 2021. The instruments in this study were demographic data, questions from knowledge factors, family income factors and religious factors. The results showed that the majority of respondents aged 31-35 years were 26 respondents (54.2%). The results of the study based on work as housewives, namely 31 respondents (64.6%), family income in the medium classification 33 respondents (68.8%), knowledge was in sufficient classification, namely 28 respondents (58.3%), the majority religion was Islam as many as 40 respondents (83.3 %). From the results of the study, it can be concluded that each factor still influences the participation of couples of childbearing age to become family planning acceptors